2008
DOI: 10.1590/s0104-12902008000100010
|View full text |Cite
|
Sign up to set email alerts
|

Conhecimento e promoção do uso do preservativo feminino por profissionais de unidades de referência para DST/HIV de Fortaleza-CE: o preservativo feminino precisa sair da vitrine

Abstract: esses profissionais pelas seguintes razões: preço elevado do insumo, a unidade não oferece o método, a mulher desconhece o método ou não vai aderir a ele, e o maior acesso ao uso do preservativo masculino, razões que merecem ser banidas do discurso profissional. Palavras-chave: Preservativos femininos; Conhecimento técnico; Desempenho profissional. AbstractThis exploratory-descriptive study took place in the 10 public reference institutions for treating sexually transmitted diseases in the city of Fortaleza, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
9

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 6 publications
0
3
0
9
Order By: Relevance
“…Knowing this, professionals should adopt strategies to arouse curiosity and encourage them. Mastering the placement steps is essential, as the method enhances autonomy, increases self-esteem, furthers negotiation ability and expands their decision-making skills (17) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Knowing this, professionals should adopt strategies to arouse curiosity and encourage them. Mastering the placement steps is essential, as the method enhances autonomy, increases self-esteem, furthers negotiation ability and expands their decision-making skills (17) .…”
Section: Discussionmentioning
confidence: 99%
“…In this context, there is an increasing need to offer the female condom as a way to expand protection possibilities and decrease gender inequalities (17) . The Ibope survey results showed the predominance of no condom use in the most recent sexual intercourse in 30.2% due to trust in the partner and 22.8% because they are married or have (a) fixed partner(s) (18) .…”
Section: Discussionmentioning
confidence: 99%
“…La Unidad Básica de Salud constituye la "puerta de entrada" del usuario, teniendo un papel potencializador en el abordaje de las DST/AIDS. La posibilidad de fortalecer relaciones de vínculo, la proximidad territorial y la integración con la red comunitaria local son factores que facilitan y amplían el acceso a la información, realización de tests de sorología, insumos de prevención, junto a traslados a servicios de referencia (5) .…”
Section: Discussionunclassified
“…Healthcare professionals were also investigated by Oliveira et al (2008), who ascertained the level of knowledge regarding female condoms and the dynamics of promotion this method, among doctors and nurses at public reference institutions for STI treatment. The results indicated that there was a knowledge deficit in relation to the basic characteristics of female condoms and how to put them on among the professionals in both categories.…”
Section: Studies On Knowledge and Behaviormentioning
confidence: 99%